Frequency of post treatment control varies by antiretroviral therapy restart and viral load criteria. (1st November 2021) - Fajnzylber, Jesse; Sharaf, Radwa; Hutchinson, John N.; Aga, Evgenia; Bosch, Ronald J.; Hartogensis, Wendy; Jacobson, Jeffrey M.; Connick, Elizabeth; Volberding, Paul; Skiest, Daniel J.; Margolis, David; Sneller, Michael C.; et al.
Abstract : N/A: Clinical trials including an analytical treatment interruption (ATI) are vital for evaluating the efficacy of novel strategies for HIV remissions. We briefly describe an interactive tool for predicting viral rebound timing in ATI trials and the impact of posttreatment controller (PTC) definitions on PTC frequency estimates. A 4-week viral load threshold of 1000 cps/ml provides both high specificity and sensitivity for PTC detection. PTC frequency varies greatly based on the definition of a PTC. Abstract : Supplemental Digital Content is available in the text